2017
DOI: 10.1016/j.jcou.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of barley and yeast β-glucan aerogels for drug delivery by supercritical fluids

Abstract: A B S T R A C TPolysaccharide aerogels are a good alternative as carriers for drug delivery, since they allow high loading of the active compounds in matrices that are non-toxic, biocompatible and from a renewable feedstock. In this work, barley and yeast β-glucans aerogels were produced by gelation in aqueous solution, followed by solvent exchange and drying with supercritical CO 2 . First, viscoelastic properties and melting profile of the hydrogels were determined. Then, the obtained aerogels were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The properties of CNF aerogels such as their biodegradability, biocompatibility, low toxicity and renewability have had an impact on the prospects of aerogels in a wide range of biological and medical applications under investigation ( Table 4 ). CNF aerogel has been tested in diverse medical applications such as biosensing, tissue engineering [ 94 ] and drug delivery [ 95 ].…”
Section: Cellulose Nanofibre (Cnf) Aerogels In Medical Applicationmentioning
confidence: 99%
“…The properties of CNF aerogels such as their biodegradability, biocompatibility, low toxicity and renewability have had an impact on the prospects of aerogels in a wide range of biological and medical applications under investigation ( Table 4 ). CNF aerogel has been tested in diverse medical applications such as biosensing, tissue engineering [ 94 ] and drug delivery [ 95 ].…”
Section: Cellulose Nanofibre (Cnf) Aerogels In Medical Applicationmentioning
confidence: 99%
“…These aerogel-based microparticles displayed significantly enhanced drug release properties. Salgado et al 90 produced barley and yeast β-glucans aerogels by a gelation process in aqueous solution, followed by solvent exchange and drying with supercritical CO 2 , which were used for acetylsalicylic acid loading and release. Lopez-Iglesias et al 49 reported chitosan-based aerogel beads with a fibrous structure, which showed high porosity (>96%) and large surface area (>200 m 2 /g).…”
Section: Aerogel-based Biomaterials For Drug Deliverymentioning
confidence: 99%
“…Hydrogels of two beta-glucans were dried with scCO2 to produce aerogels for tissue engineering purposes. These aerogels were loaded with acetylsalicylic acid [ 107 ] or with dexamethasone [ 108 ]. High water uptakes were obtained for both glucans (between 600% and 1400%, depending on the concentration and glucan type).…”
Section: Exopolysaccharides For Producing Ddssmentioning
confidence: 99%
“…These differences in water uptake promoted a different sustained drug release over 24 h. Since their specific surface areas were always higher than 100 m 2 ·g −1 , this article demonstrates the possibility of producing aerogels via scCO 2 drying. However, the Young´s modulus of the obtained aerogels was between 8–15 kPa and their application for tissue engineering must be chosen carefully [ 107 , 108 ].…”
Section: Exopolysaccharides For Producing Ddssmentioning
confidence: 99%